Globalisation and Ireland's export performance - Frances Ruane; Iulia Siedschlag; Gavin Murphy (The Economic and Social Research Institute (ESRI), 2013)
This paper provides empirical evidence on Ireland's export performance in the context of increased globalisation over the past ten years. Using insights from recent contributions to international trade and economic growth theories, we first examine patterns and changes of revealed comparative advantages for Ireland's exports of goods and services. We then investigate whether Irish exports have specialised in fast growing industries and markets in world exports over the period. Third, we analyse determinants of export performance dynamics focusing on product and market structures and competitiveness effects. Finally, to put Ireland's export performance into perspective, we compare this evidence with recent developments in other selected European small open economies.
Keywords: F14; F15; F43; 330; Globalisation; Competitiveness; Export Performance Dynamics